2010
DOI: 10.1007/s12672-010-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol Inhibits Progesterone-Dependent Tissue Factor Expression and Activity in Breast Cancer Cells

Abstract: 2-Methoxyestradiol (2ME) is an endogenous metabolite of 17β-estradiol with antiangiogenic and antitumor properties, although its mechanisms of action remain unclear. Progestins in hormone replacement therapy increase the risk of breast cancer. Progesterone also enhances the procoagulant activity and invasive potential of progesterone receptor (PR)-positive breast cancer cell lines, an effect largely mediated by induction of tissue factor (TF), the cellular activator of the coagulation cascade. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Although this is not the first observation that progesterone can regulate PAR1, this is, to our knowledge, the first to demonstrate regulation in breast cancer or mammary glandderived cells. It has not escaped our notice that the timing and mechanism of PAR1 regulation by progesterone is remarkably similar to the progesterone regulation of TF in both T47D and ZR-75 cells (Kato et al 2005b, Quezada et al 2010, Henriquez et al 2011. Advanced breast cancer is associated with a hypercoagulable state that may be triggered or enhanced by the presence of TF and PAR1 on the surface of cancer cells (Ruf & Mueller 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Although this is not the first observation that progesterone can regulate PAR1, this is, to our knowledge, the first to demonstrate regulation in breast cancer or mammary glandderived cells. It has not escaped our notice that the timing and mechanism of PAR1 regulation by progesterone is remarkably similar to the progesterone regulation of TF in both T47D and ZR-75 cells (Kato et al 2005b, Quezada et al 2010, Henriquez et al 2011. Advanced breast cancer is associated with a hypercoagulable state that may be triggered or enhanced by the presence of TF and PAR1 on the surface of cancer cells (Ruf & Mueller 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, 2-ME impacts on various physiological and pathological conditions like muscle contraction or pre-eclampsia [18,31,32,34]. Studies in vitro and in vivo revealed that 2-ME at pharmacological concentrations inhibited the growth of various cancer types, including colon [35], breast [36], or lung [37]. On the contrary, there are only a few data concerning physiological activity of 2-ME [17,38].…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer activity of 2‐ME was also determined in various experimental models in vitro. 2‐ME was reported to be an effective chemotherapeutic towards colon, kidney, pancreas, breast, lung, and osteosarcoma cells (Gorska et al, , ; Maran et al, , ; Matei et al, ; Quezada et al, ; Schumacher & Neuhaus, ; Snoeks, Mol, Que, Kaijzel, & Loewik, ; Zou et al, ). Previously, we have evidenced that 2‐ME may be a physiological anticancer agent (Gorska et al, ).…”
Section: Introductionmentioning
confidence: 99%